2012
DOI: 10.1002/ibd.21873
|View full text |Cite
|
Sign up to set email alerts
|

Salvinorin A has antiinflammatory and antinociceptive effects in experimental models of colitis in mice mediated by KOR and CB1 receptors*

Abstract: Our results suggest that the drugs based on the structure of SA have the potential to become valuable antiinflammatory or analgesic therapeutics for the treatment of GI diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 36 publications
0
67
0
Order By: Relevance
“…Originally, SA was identified as a potent KOR agonist, but recently it has also been shown to possess, unusual for plantderived opioids, the ability to activate CB receptors in in vitro and in vivo assays (Roth et al, 2002;Capasso et al, 2008;Fichna et al, 2009aFichna et al, , 2012Aviello et al, 2011). Here, we observed that the inhibitory effect of PR-38 on twitch contractions in mouse colon in vitro and on the GI motility in vivo was blocked by MOR and KOR antagonists.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Originally, SA was identified as a potent KOR agonist, but recently it has also been shown to possess, unusual for plantderived opioids, the ability to activate CB receptors in in vitro and in vivo assays (Roth et al, 2002;Capasso et al, 2008;Fichna et al, 2009aFichna et al, , 2012Aviello et al, 2011). Here, we observed that the inhibitory effect of PR-38 on twitch contractions in mouse colon in vitro and on the GI motility in vivo was blocked by MOR and KOR antagonists.…”
Section: Discussionmentioning
confidence: 67%
“…This suggests that, among all the receptors targeted by PR-38, MOR is mostly responsible for its analgesic activity in abdominal pain models, and implicates the lack of the synergistic effect Novel Salvinorin A Analog PR-38 in IBS upon activation of opioid and CB receptors for the induction of analgesia. We have shown previously that the analgesic effect produced by SA in the same pain model was mediated by KOR and CB1 (Fichna et al, 2012). Our observations demonstrate that the modification of the SA molecule, which resulted in the increased affinity for MOR, changed the mechanism of the action of the compound and shifted the equilibrium toward MOR in production of the analgesic effect, which is crucial for further structure-activity relationship studies.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The TNBS-induced mouse model of colitis is a wellestablished acute animal model of CD, as described earlier (Fichna et al, 2012a). On day 0, mice (5-8 per treatment group) were lightly anesthetized using 1% isoflurane (Aerrane; Baxter Healthcare Corp., Deerfield, IL), and TNBS (4 mg in 0.1 ml of 30% EtOH in 0.9% NaCl) was administered into the distal colon using a catheter (silicone pusher).…”
Section: Methodsmentioning
confidence: 99%
“…TNBS (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) was applied to induce colitis, as previously described (12,21,22). In brief, mice were fasted for 16 h, and anesthetized with 1% isoflurane.…”
Section: Animalsmentioning
confidence: 99%